Association of ankylosing spondylitis activity indicators in a Russian population of patients with STAT4 rs7574865 gene polymorphism - M. Yu. Krylov; A. S. Starkova; E. Yu. Samarkina; T. V. Dubinina; Sh. F. Erdes (Современная ревматология, 2019)
Family and twin studies have shown that ankylosing spondylitis (AS) has a hereditary nature that is based on a strong association with the leukocyte antigen HLA-B27. However, only 1–5% of HLA-B27 carriers develop AS, which indicates that there are other genetic markers involved in the formation of a predisposition to this disease. A number of genome-wide association studies have convincingly confirmed the role of the STAT4 gene. This gene encodes the protein – the signal transducer and activator of transcription (STAT) protein, which is a predisposing factor for the development of many autoimmune diseases. There are not so many studies of the relationship of STAT4 polymorphisms to the predisposition to AS, and there are no these studies regarding the Russian population.Objective: to study whether there is a possible association of STAT4 rs7574865 gene polymorphism with the predisposition to AS and to assess the activity of this disease using BASDAI and ASDAS scores in the Russian patient population.Patients and methods. A cohort of 203 individuals, including 100 patients (79 men and 21 women) with AS, and 103 healthy volunteers (a control group) was surveyed. Age, gender, duration, and specific features of AS onset, ESR, and CRP levels were assessed. BASDAI and ASDAS scores were calculated to evaluate disease activity.Results and discussion. There was a significant relationship between STAT4 polymorphism and C-reactive protein (CRP) levels and BASDAI and ASDAS-CRP scores. The TT genotype carriers had significantly higher mean activity indices compared to the GG (p=0.001) and GT (p=0.005) genotype carriers for CRP, BASDAI (p=0.0001 and p=0.009, respectively) and ASDAS-CRP (p=0.009 and p=0.001, respectively). High disease activity (BASDAI >4 and ASDAS-CRP >3.5) was also associated with the high frequency of the T allele (p=0.046 and p=0.004, respectively). The value of STAT4 rs7574865 gene polymorphism in the pathogenesis of autoimmune diseases is confirmed by a study in which the T allele in STAT4 rs7574865 enhances mRNA transcription and protein expression. Italian authors have shown that there is a relationship between the minor T allele of rs7574865 and the high risk of arthritis. We have previously established a relationship between the T allele and the predisposition to diffuse systemic scleroderma, interstitial lung damage, and elevated anti-topoisomerase I antibody levels.Conclusion. The present study has shown for the first time a significant association of STAT4 rs7574865 polymorphism with the main AS activity indicators: CRP levels, BASDAI and ASDAS-CRP scores. The studied polymorphism may be a new genetic marker for predicting the severity of AS.